Comportamento de forrageamento do pernilongo-de-costas-brancas, Himantopus melanurus (Vieillot, 1817) (Aves: Recurvirostridae) em Santa Gertrudes, SP, Brasil - Gussoni, Carlos Otávio A. [UNESP]; Guaraldo, André C. [UNESP] (My University, 2006)
The foraging behavior of two White-backed stilts (Himantopus melanurus) was studied in a lake at the municipality of Santa Gertrudes, state of São Paulo, Brazil. The foraging strategies observed were classified in two categories: pluging (65.8% of total maneuvers) and pecking (34.3%). Only in 26.8% of the foraging maneuvers the individuals captured preys (72.9% by plunging and 27.1% by pecking). When comparing both strategies, plunging was successful 29.7% of the times, but pecking only 21.2%. At the study site, individuals foraged only up to 20 m away from the lake margin. The foraging area exploited by the White-backed stilts was estimated in about 720 m 2. Foraging activities lasted since before sunrise until after sunset. © 2006 Instituto de Ciências Biológicas - UFMG.
Foraging behavior of the White-backed stilt, Himantopus melanurus (Vieillot, 1817) (Aves: Recurvirostridae) in Santa Gertrudes, SP, Brazil
Keywords: Foraging behavior; Pecking; Plunging; White-backed stilt; diving behavior; feeding ground; foraging behavior; lacustrine environment; prey capture; wader; Brazil; Santa Gertrudes; Sao Paulo [Brazil]; South America; Aves; Charadriidae; Himantopus melanurus